DESCRIPCIÓN DE LA LARVA DE PARACLES AZOLLAE (BERG, 1877) (LEPIDOPTERA: EREBIIDAE) - Morelli, Enrique; Diez, Andrea; Bentancur-Viglione, Gabriela (Boletín de la Sociedad Zoológica del Uruguay, 2018)
Description of the larva of Paracles azollae (Berg, 1877) (Lepidoptera: Erebiidae). The description of immature stages for aquatic lepidopteran species is fragmentary and almost non-existent for the American continent. The larvae of the aquatic species of Arctiinae are recognized by the presence of secondary setae and warts, which give them a hairy appearance. The Paracles genus is present in the Neotropical regions, where Uruguay and Argentina are considered the southern limit of their distribution. For Uruguay are cited the species Paracles azollae (Berg, 1877), P. tenuis Berg, 1877, P. burmeisteri (Berg, 1877), P. uruguayensis (Berg, 1886), P. cajetani (Rothschild, 1910) and P. vulpina (Hübner, [1825]). The mature larva of P. azollae is characterized by a protoraxic shield with main setae and warts. T2 and T3 with dorsal respiratory plastron complex, and warts with long and thick feathery setae. A1-2 with a complex dorsal plastron with setae in pinaculum. A3-8 with plastron and setae in pinaculum. A9 with complex plastron and warts. A10 with dorsal wart. The presence and number of warts, the number and shape of setae and the location of the plastron are presented as anatomical characters for the specific determination of the Paracles genus.